PENGARUH LATIHAN KEKUATAN OTOT TUNGKAI TERHADAP JAUHNYA TENDANGAN PADA PEMAIN SEPAK BOLA PSDKU ARU - Maita, Gidion S; Syaranamual, Jusak; Somarwain, Falerius. (JARGARIA SPRINT: Journal Science of Sport and Health, 2023)
Football game is one of the sports that is of interest to Patimura University students of the Outside Main Campus Study Program (PSDKU ARU), who often appear with PSDKU ARU soccer players at soccer championships held in the city of Dobo. As well as in the student league "The Effect of Limb Muscle Strength Training on the Distance of Kicks in Psdku Aru Soccer Players" which amounted to 20 people, the collection of data sources in this study was through long-distance kick test data before being treated and after being treated. The test result from observation = 12.129 is greater than ttable. For levels of 5% and 1% (12,129 > 1,729 and > 2,539). Thus the null hypothesis (Ho) which states that there is no effect of weight training using body weight on increasing leg muscle strength in PSDKU ARU soccer players, is rejected and the alternative hypothesis (Ha) is accepted. The results of research and discussion are Squats, Hillrice, Step exercises. -Up, and Split Leg. To objectively improve the ability to shoot distance for PSDKU ARU soccer players. The intensity of exercise was 50% in weeks I and II, weeks III and IV was 75%, and weeks V and VI were 100%.